ERNICA Consensus conference on the management of patients with long-gap esophageal Atresia: Perioperative, Surgical, and Long-Term Management - Dingemann, Carmen; Eaton, Simon; Aksnes, Gunnar; Bagolan, Pietro; Cross, Kate M.; Coppi, Paolo De; Fruithof, JoAnne; Gamba, Piergiorgio; Goldschmidt, Imeke; Gottrand, Frederic; Pirr, Sabine; Rasmussen, Lars; et al. (European journal of pediatric surgery, 2020)
Introduction: Evidence supporting best practice for long-gap esophageal atresia is limited. The European Reference Network for Rare Inherited Congenital Anomalies (ERNICA) organized a consensus conference on the management of patients with long-gap esophageal atresia based on expert opinion referring to the latest literature aiming to provide clear and uniform statements in this respect. Materials and Methods: Twenty-four ERNICA representatives from nine European countries participated. The conference was prepared by item generation, item prioritization by online survey, formulation of a final list containing items on perioperative, surgical, and long-term management, and literature review. The 2-day conference was held in Berlin in November 2019. Anonymous voting was conducted via an internet-based system using a 1 to 9 scale. Consensus was defined as ≥75% of those voting scoring 6 to 9. Results: Ninety-seven items were generated. Complete consensus (100%) was achieved on 56 items (58%), e.g., avoidance of a cervical esophagostomy, promotion of sham feeding, details of delayed anastomosis, thoracoscopic pouch mobilization and placement of traction sutures as novel technique, replacement techniques, and follow-up. Consensus ≥75% was achieved on 90 items (93%), e.g., definition of long gap, routine pyloroplasty in gastric transposition, and avoidance of preoperative bougienage to enable delayed anastomosis. Nineteen items (20%), e.g., methods of gap measurement were discussed controversially (range 1-9). Conclusion: This is the first consensus conference on the perioperative, surgical, and long-term management of patients with long-gap esophageal atresia. Substantial statements regarding esophageal reconstruction or replacement and follow-up were formulated which may contribute to improve patient care.